Geochronology of Hydrothermal Processes Leading to the Formation of the Au–U Mineralization at the Rompas Prospect, Peräpohja Belt, Northern Finland: Application of Paired U–Pb Dating of Uraninite and Re–Os Dating of Molybdenite to the Identification of Multiple Hydrothermal Events in a Metamorphic Terrane - Ferenc Molnár; Hugh O’Brien; Holly Stein; Nick Cook (Minerals, 2017)
The Peräpohja belt comprises a greenschist to amphibolite facies; multiply-folded supracrustal sequence of quartzites; mafic volcanics; carbonate rocks; black shales; mica schists and greywackes deposited from ca. 2.44 Ga to 1.92 Ga; during protracted rifting of the Archaean basement. Metamorphism and multiple folding of the basin fill occurred during the Svecofennian orogeny (1.92–1.80 Ga). The Rompas Au–U mineralization is hosted within deformed and metamorphosed calcsilicate veins in mafic volcanics. Textural evidence suggests that deposition and periods of uraninite re-mobilization were followed by localized hydrocarbon-bearing fluid flow which produced pyrobitumen crusts around grains of uraninite. Gold precipitated during the latest hydrothermal event at around 1.75 Ga. In situ U–Pb dating of uraninite by laser ablation inductively coupled mass spectroscopy (LA-ICP-MS), and Re–Os dating of molybdenite, indicate that primary hydrothermal uranium mineralization forms two age clusters; about 2.03–2.01 and 1.95–1.94 Ga. Resetting of the U–Pb system and precipitation of new generations of uraninite are associated with major deformation and metamorphic stages of the Svecofennian orogeny at 1.91–1.89 Ga, 1.85 Ga, and 1.80 Ga. Gold deposition was synchronous with the emplacement of the 1.75–1.78 Ga late/post-orogenic granitoids. The gold-producing hydrothermal event is also recorded by Re–Os dating of molybdenite from the gold-bearing Mg-metasomatized metasedimentary and metavolcanic units at the Palokas prospect; a few kilometres from Rompas. Results of this study confirm that some domains in the structure of uraninite may preserve the original crystallization age, despite an overprinting amphibolite facies metamorphic and other hydrothermal events. The study supports the utility of in situ U–Pb dating of uraninite and the ability of Re–Os dating to assist in sorting out different hydrothermal events in areas with complex tectonic; magmatic and metamorphic histories.